CD40 ligation induces Apo-1/Fas expression on human B lymphocytes and facilitates apoptosis through the Apo-1/Fas pathway (The Rockefeller University Press, 1995)
The Apo-1/Fas antigen (CD95) mediates programmed cell death of lymphocytes when bound by Fas ligand or anti-Apo-1/Fas antibody. In contrast, the CD40 antigen provides a potent activation and survival signal to B lymphocytes when it is engaged by its T cell ligand (CD40L, gp39) or cross-linked by anti-CD40 antibody. In this study, we use human tonsillar B cells and the Ramos Burkitt's lymphoma B cell line, which serves as a model for human germinal center B lymphocytes, to study the effectors of Apo-1/Fas expression and apoptosis of human B cells. We found that Apo-1/Fas expression was upregulated on both malignant and normal human B lymphocytes after CD40 ligation induced by (a) cognate T helper-B cell interaction mediated by microbial superantigen (SAg); (b) contact-dependent interaction with CD40L+, but not CD40L- Jurkat mutant T cell clones; and (c) monoclonal anti-CD40, but not any of a panel of control antibodies. Enhanced B cell Fas/Apo-1 expression is functionally significant. Coculture of Ramos Burkitt's lymphoma line cells with irradiated SAg-reactive CD4+ T cells with SAg or CD40L+ Jurkat T cells results in B cell apoptosis, evidenced by reduced cell viability and DNA laddering. This process is augmented by the addition of anti-Apo-1/Fas monoclonal antibody, consistent with an acquired susceptibility to Apo-1/Fas-mediated apoptosis. These data support an immunoregulatory pathway in which seemingly contradictory signals involving the B cell proliferation/survival antigen CD40, as well as the Apo-1/Fas molecule, which mediates programmed cell death of lymphocytes, are linked in the process of human B cell activation.